PENGEMBANGAN SUMBER DAYA PENDIDIKAN DI MADRASAH ALIYAH NEGERI (MAN) KABUPATEN BIREUN - Mudassir Mudassir (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2016)
In line with the sharp competition due to technological development and environment the that is so dramatically in all aspects of human life, then every educational institution need professional human resources of education in order to provide excellent service and value. In other words, educational institutions are should not only able to provide satisfactory service (customer satisfaction) but also oriented on the value (customer value). The research results show that the development of human resources of education in MAN Bireuen consist of improving human resource education through teacher training. The necessary training is tailored to the needs of teachers. The training was carried out to take upgrade teachers’ performance that was low. Several obstacle faced in the development of education human resources the lack of teacher training and teachers’ knowledge in the field of information technology (IT). To solve these problems can be done through training program of teaching profession (PLPG) which aims to create a professional teacher and Teacher Competency Test (UKG). The Indonesian government should improve the quality of LPTK as teacher producers, and conduct teacher training on information and communication echnology (ICT) intensively.